Penerapan Konsep Keadaan Serupa dan Pengaturannya dalam Klausul Perlakuan Nasional - Priskilla Chrysentia (Universitas Katolik Widya Karya Malang, 2023)
National treatment is one of the fundamental standards in the implementation of foreign direct investment. An important element determining the applicability of national treatment standard is the existence of ‘like circumstances’ between foreign and domestic investors. However, the application of ‘like circumstances’ concept is often inconsistent, due to the absence of touchstones necessary to determine the ‘like circumstances’ itself. This study analyzes the significance of the application of ‘like circumstances’ concept in national treatment standard and its regulation in national treatment clauses in international investment agreements, showing that the absence of provisions on the touchstones to determine ‘like circumstances’ might contribute to the inconsistency of the application of national treatment standard, thus the insertion of the touchstones to determine ‘like circumstances’ is necessary.